Physiological and performance responses to a training camp in the heat in professional Australian football players - Racinais, S.; Buchheit, M.; Bilsborough, J. C.; Bourdon, P. C.; Cordy, J. T.; Coutts, A. J. (International Journal of Sports Physiology and Performance, 2014)
Purpose: To examine the physiological and performance responses to a heat-acclimatization camp in highly trained professional team-sport athletes. Methods: Eighteen male Australian Rules Football players trained for 2 wk in hot ambient conditions (31-33°C, humidity 34-50%). Players performed a laboratory-based heat-response test (24-min walk + 24 min seated; 44°C), a YoYo Intermittent Recovery Level 2 Test (YoYoIR2; indoor, temperate environment, 23°C) and standardized training drills (STD; outdoor, hot environment, 32°C) at the beginning and end of the camp. Results: The heat-response test showed partial heat acclimatization (eg, a decrease in skin temperature, heart rate, and sweat sodium concentration, P < .05). In addition, plasma volume (PV, CO rebreathing, +2.68 [0.83; 4.53] mL/kg) and distance covered during both the YoYoIR2 (+311 [260; 361] m) and the STD (+45.6 [13.9; 77.4] m) increased postcamp (P < .01). None of the performance changes showed clear correlations with PV changes (r < .24), but the improvements in running STD distance in hot environment were correlated with changes in hematocrit during the heat-response test (r = -.52, 90%CI [-.77; -.12]). There was no clear correlation between the performance improvements in temperate and hot ambient conditions (r < .26). Conclusion: Running performance in both hot and temperate environments was improved after a football training camp in hot ambient conditions that stimulated heat acclimatization. However, physiological and performance responses were highly individual, and the absence of correlations between physical-performance improvements in hot and temperate environments suggests that their physiological basis might differ.